2005
DOI: 10.1080/08035250510031151
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and morphological changes after hypoxic-ischaemic injury in preterm lambs

Abstract: Our results suggest that regional cerebral blood flow and the presence of apoptotic cells, 3 h after hypoxic-ischemic injury, are correlated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
(29 reference statements)
2
23
0
Order By: Relevance
“…This was associated with significant reduction of excitatory amino acids level in the striatum suggestive of more favorable neurologic outcome in Re-O 2 HI-piglets (5). In preterm lambs subjected to HI-insult the severity of cerebral regional hypoperfusion strongly correlated with increased apoptotic cell death-rate (21). In our study, improved late neurologic outcome in Re-O 2 mice compared with Re-Air mice may be secondary to the more efficient restoration of hypoxia-depressed CBF during Re-O 2 .…”
supporting
confidence: 49%
“…This was associated with significant reduction of excitatory amino acids level in the striatum suggestive of more favorable neurologic outcome in Re-O 2 HI-piglets (5). In preterm lambs subjected to HI-insult the severity of cerebral regional hypoperfusion strongly correlated with increased apoptotic cell death-rate (21). In our study, improved late neurologic outcome in Re-O 2 mice compared with Re-Air mice may be secondary to the more efficient restoration of hypoxia-depressed CBF during Re-O 2 .…”
supporting
confidence: 49%
“…A significant proportion of fetuses had ACA PI values below the 5th percentile, despite presenting an MCA PI within the normal range and hence not showing cerebral blood flow redistribution as currently defined. Differences in the response to hypoxia of different fetal cerebral vascular territories are also supported by experimental research in which the brain of fetal lambs showed an internal redistribution of the blood flow in relation to the degree of the hypoxic insult [3] .…”
Section: Introductionmentioning
confidence: 77%
“…Experimental and human studies coincide in the regionalization of vascular redistribution showing increased brain perfusion in frontal lobe, basal ganglia and cerebellum [45,46]. The preferential involvement of the frontal lobe in fetal growth restriction has been reported by different authors.…”
Section: Discussionmentioning
confidence: 99%